Chemotherapeutic Nanoparticle-Based Liposomes Enhance the Efficiency of Mild Microwave Ablation in Hepatocellular Carcinoma Therapy - Wu, Songsong; Zhang, Dongyun; Yu, Jie; Dou, Jianping; Li, Xin; Mu, Mengjuan; Liang, Ping (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) is the third leading cause of death from cancer, and the 5-year overall survival (OS) rate for HCC remains unsatisfying worldwide. Microwave ablation (MWA) is a minimally invasive therapy that has made progress in treating HCC. However, HCC recurrence remains problematic. Therefore, combination therapy may offer better outcomes and enhance MWA efficiency through improved tumor control. We have developed doxorubicin-loaded liposomes (DNPs) as an efficient nanoplatform to enhance MWA of hepatocellular carcinoma even at the mild ablation condition. In this study, we demonstrated that the uptake of DNPs by HCC cells was increased 1.5-fold compared with that of free DOX. Enhanced synergism was observed in the combination of DNPs and MWA, which induced nearly 80% cell death. The combination of mild MWA and DNPs enhanced the ablation efficiency of HCC with significant inhibition of liver tumors and accounted for the longest survival rate among all groups. A much higher accumulation of the DNPs was observed in the transitional zone than in the ablation zone. No apparent systemic toxicity was observed for any of the treatments after 14 days. The present work demonstrates that DNPs combined with MWA could be a promising nanoparticle-based therapeutic approach for the treatment of hepatocellular carcinoma and shows potential for future clinical applications.